German banks on the way to climate neutrality? A review of the situation - Maike Wilhelm; Ali Aydemir; Clemens Rohde (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2023)
Previous international climate change agreements have primarily been driven by states, such as the UN Conference on Environment and Development in Rio de Janeiro in 1992, followed by the Kyoto Protocol in 1997 and the Paris Agreement in 2015. Perhaps due to the national focus of these agreements, discussions and actions to date have mainly centred on direct carbon emissions from households, transport and industry. However, it is important not to overlook the significant potential for the financial industry to contribute towards combating climate change. Through their lending activities, they determine which economic activities receive financing and which do not. This economic power is needed to achieve the Paris climate goals. While Germany's Climate Protection Act provides a framework for meeting these goals, it does not impose specific requirements on banks. However, German banks have voluntarily committed to fulfilling their responsibilities in regards to climate policy. In this study, we analyze the goals and measures that German banks plan to pursue in their efforts to combat climate change based on self-statements found in their strategy papers.
Keywords: 330; green finance; sustaible finance; policy measures